Form Factors or International Law Standards: Legitimation of Law or Legalization of the Centers of Force? - Kuzmin, Andrey (Research Papers, 2018)
The article is devoted to the problems of international legal standards. Research objective is exploring the possibility of using in science of the category "form factor". The main results of the article are that form factors of international law are the accession parameters established in the regulations of the national law extending to the sphere of the interstate relations. А study of this category is conducted first.
Keywords: Form factor; International legal standards; National legislation